Powerful CEOs and CSR performance: Empirical evidence from France - Yousfi, Ouidad; Loukil, Nadia; Béji, Rania (Management international / International Management / Gestiòn Internacional, 2022)
This study analyses the impacts of CEO’s traits on CSR performance. It is conducted on listed firms on the SBF120. The major outcomes of the studies are as follows: First, powerful CEOs appear as having significant effects only on specific CSR areas. Second, CEOs who graduated business, science or engineering degrees decrease the firm’s social performance. Also, powerful CEOs in family businesses are prone to increase the firm’s commitment in CSR while senior CEOs are likely not to feel concerned by CSR.